COMMON-SENSE LEGITIMATION OF INFORMAL PRACTICES IN PRESENT-DAY SERBIA - JOVANOVIĆ, MILOŠ (Society Register, 2019)
As a part of a larger research within the Horizon 2020 project Closing the Gap Between Formal and Informal Institutions in the Balkans, 38 semi-structured interviews with citizens of Serbia have been conducted in the period July – October 2017. These comprise the database used for analysis of “narratives of informality” – stories of how the research participants legitimize (or rationalize) informal practices (using connections and acquaintances to “get things done”, giving/receiving bribe, exchange of favors, etc.), supplemented by the analysis of participants’ attitudes towards informal practices, particularly when using them themselves. An insight into the respondents’ ideas of informality was gained through describing and understanding doxa – beliefs of an individual as “a quasi-perfect correspondence between the objective order and the subjective principles of organization (with which) the natural and social world appear as self-evident” (Bourdieu) or senso comune (Gramsci) – “naturalized”, unreflected, practical knowledge taking the form of self-explanatory content of common sense, that which is taken for granted, what “everybody knows“, the knowledge of the world that is undisputed – “just the way it is”, the domain of indefinite beliefs and incoherent views of the world, the knowledge which “legitimizes with the absence of legitimizing”. The assumption is that the “quality” of doxa, in the sense of its positive or negative orientation, has a large impact on the possibility of changes in formal practices and procedures – in some cases serving as a stimulus for change, and as an obstacle to changes in others – situations in which the new/imported rules remain “empty shells” with little influence in social life.